Australian Renewable Energy Law: Carbon Lock-in or Clean Energy Transition?: The pursuit of policy stability and energy security at higher levels of renewable generation. Issue 1 (December 2018) - Prest, James
Abstract : This article critically analyses recent developments in Australia's renewable energy law and policy. It identifies seven retrograde steps taken in energy and climate law in Australia in the last five years. Barriers to clean energy law - in the form of recurring narratives employed against the rise of renewable energy across Australia - are examined. Increased levels of renewable energy are portrayed by opponents as a threat to the security and reliability of electricity supply. Yet, the nation is currently experiencing a major renewable energy investment boom, supported by regional policy initiatives that are driving innovation, most recently in energy storage.